2018
DOI: 10.1177/1352458518790417
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl fumarate therapy suppresses B cell responses and follicular helper T cells in relapsing-remitting multiple sclerosis

Abstract: In summary, these data suggest an anti-inflammatory role of DMF and its metabolite MMF on the B cell compartment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 28 publications
5
19
1
Order By: Relevance
“…It was not addressed whether this increase was due to an increase of transitional B cells or to a suppression of their differentiation to naïve mature B cells. This finding is in accordance with previous studies also showing an increase of transitional B cells following 12 months of treatment, although our work is the first reporting this effect after only 3 months of DMF therapy.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…It was not addressed whether this increase was due to an increase of transitional B cells or to a suppression of their differentiation to naïve mature B cells. This finding is in accordance with previous studies also showing an increase of transitional B cells following 12 months of treatment, although our work is the first reporting this effect after only 3 months of DMF therapy.…”
Section: Discussionsupporting
confidence: 94%
“…On the other hand, we also observed a selective decrease on circulating memory B cells (both switched and preswitched), in parallel with an increase of naïve B lymphocytes, in accordance with previous publications . B cells can produce pro‐inflammatory cytokines, and treatments depleting the B‐cell compartment such as rituximab (anti‐CD20 monoclonal antibody) have demonstrated beneficial effects on MS patients.…”
Section: Discussionsupporting
confidence: 91%
“…Such reductions affect mostly cytotoxic T cells, effector/central memory T cells, Th1 cells, Th17 cells, mucosa-associated lymphoid tissue (MALT) cells follicular T cells with a Tfh1/17 phenotype, antigen experienced and memory B cells, and B cells producing TNF. Immunoregulatory CD56 bright NK-cells, naïve T and B cells, Th2 cells, FoxP3 + Tregs, and follicular T cells with a Tfh2 phenotype are increased (151, 153155, 157162). Such a pro-tolerogenic shift is associated with NEDA in MS patients (158); higher levels of the NRF2 target gene NAD(P)H quinone dehydrogenase 1 (NQO1) was also associated with NEDA status after 1 year of DMF treatment (151).…”
Section: Dimethyl Fumarate (Dmf)mentioning
confidence: 99%
“…Moreover, several studies confirmed that the orally given agent increases the proportion of transitional B cells while reducing memory and antigen-activated B cells with a disproportionate decrease of plasmablasts [ 128 , 131 , 132 ]. In this line, B cells of treated patients produce less interleukin-6 and tumor necrosis factor, resulting in a more anti-inflammatory cytokine profile and reduced levels of serum interleukin-6 [ 133 , 134 ]. In addition, the expression of molecules involved in antigen presentation (CD40, CD80 and CD86) was found to be decreased in patients treated with dimethyl fumarate [ 128 , 131 ].…”
Section: Effects Of Ms Medications On Peripheral B Cells In Humansmentioning
confidence: 99%